The Adaptation of the Moral Integrity Scale into Turkish and Analysis of the Psychometric Features - (:unkn) unknown (My University, 2020)
The aim of this study is to adapt the Moral Integrity Scale developed by Sclenker (2008) to Turkish and conduct its psychometric analysis. The scale items were translated into Turkish by five specialists in the first place. After the language structure, culture suitability and understandability of the items were examined by the two experts, the items agreed upon were translated back to their original language by the two translation experts. After the positive evaluations of the experts, the final version of the scale items was decided. During the adaptation process of the study, data were collected from 470 people for exploratory factor analysis; from 248 people for confirmatory factor analysis and from 100 people for criterion validity. In this context, Exploratory Factor Analysis (AFA) was used to test the construct validity of the scale first. As a result of the exploratory factor analysis, it is seen that the moral integrity scale explains 52,127% of the variance as one dimension. Confirmatory factor analysis (CFA) was then performed to test the construct validity of the scale. The one-dimensional and 18-item structure of the Moral Integrity Scale was analyzed with DFA and accepted fit indices were obtained (X2 / sd = 2.745; p <.001; RMSEA = 0.061; S-RMR = 0.051; NFI = 0.929; CFI = 0.954; GFI = 0.915; RFI = 0.919). In order to calculate the scale reliability, the Cronbach Alpha (α) internal consistency coefficients and the difference between the lower and upper scores of 27% were examined. For the Moral Integrity Scale, the internal consistency coefficient Cronbach’s Alpha value was determined as 961. At the same time, the moral identity scale was used for criterion validity and a significant positive relationship was obtained with the two sub-dimensions of this scale. The total score obtained from the scale gives the person’s moral integrity score. According to all these results, it is understood that the Moral Integrity Scale has sufficient validity and reliability values.

Bu çalışmanın amacı, Schlenker (2008) tarafından geliştirilen Ahlaki Bütünlük Ölçeği’ni Türkçe’ye uyarlamak ve psikometrik incelemesini yapmaktır. Ölçek maddeleri ilk etapta, alanında uzman beş kişi tarafından Türkçe ’ye çevrilmiştir. İki uzman tarafından maddelerin dil yapısı, kültüre uygunluğu ve anlaşılabilirliği incelendikten sonra üzerinde mutabık kalınan maddeler, iki çeviri uzmanı tarafından tekrar orijinal diline çevrilmiştir. Uzmanların olumlu değerlendirmelerinden sonra, ölçek maddelerinin son halinde karar kılınmıştır. Çalışmanı n uyarlama sürecinde, ilki açımlayıcı faktör analizi için 470 kişiden; ikincisi doğrulayıcı faktör analizi için 248 kişiden ve üçüncüsü ölçüt geçerliği için 100 kişiden veri toplanmıştır. Bu kapsamda ilk önce ölçeğin yapı geçerliğini test etmek amacıyla Açımlayıcı Faktör Analizi (AFA) kullanılmıştır. Yapılan açımlayıcı faktör analizi sonucunda ahlaki bütünlük ölçeğinin tek boyut olarak varyansın %52,127’sini açıkladığı görülmektedir. Ölçeğin yapı geçerliliğini test etmek amacıyla daha sonra doğrulayıcı faktör analizi (DFA) yapılmıştır. Ahlaki Bütünlük Ölçeği’nin tek boyutlu ve 18 maddeli yapısı DFA ile analiz edilmiş ve kabul gören uyum indeksleri elde edilmiştir (X2/sd=2.745; p<.001; RMSEA=0.061; S-RMR=0.051; NFI=0.929; CFI=0.954; GFI=0.915; RFI=0.919). Ölçek güvenirliğini hesaplamak için Cronbach Alpha (α) iç tutarlılık katsayılarına ve %27’lik alt ve üst puanları arasındaki farka bakılmıştır. Ahlaki Bütünlük Ölçeği (ABÖ) için iç tutarlılık katsayısı Cronbach’s Alpha değeri ,961 olarak tespit edilmiştir. Aynı zamanda ölçüt geçerliği için ahlak kimlik ölçeği kullanılmış ve bu ölçeğin iki alt boyutuyla anlamlı pozitif bir ilişki elde edilmiştir. Ölçekten elde edilen toplam puan kişinin ahlaki bütünlük puanını vermektedir. Tüm bu sonuçlara göre, Ahlaki Bütünlük Ölçeği’nin (ABÖ) yeterli geçerlik ve güvenirlik değerlerine sahip olduğu anlaşılmaktadır.
Ahlaki Bütünlük Ölçeği’nin Türkçe’ye Uyarlanması ve Psikometrik Özelliklerinin İncelenmesi